Simple synthesis of the novel Cu‐MOF catalysts for the selective alcohol oxidation and the oxidative cross‐coupling of amines and alcohols. (9th September 2020) - Ghamari Kargar, Pouya; Aryanejad, Sima; Bagherzade, Ghodsieh
Abstract : A novel porous metal–organic framework {Cu2 (bbda)0.5 (Hbbda)1.5 (OAc)1.5 .8H2 O} (UoB‐5) was synthesized under ultrasound irradiation by employing a new Schiff base ligand H2 bbda (4, 4′(1, 4‐phenylene bis (azanylylidene)) bis (methanylylidene))dibenzoic acid) and was fully characterized. The microporous nature of UoB‐5 was confirmed by gas‐sorption measurements. This framework acted as a highly effective heterogeneous catalyst for the alcohol oxidation reaction with tert ‐butyl hydroperoxide ( t ‐BuOOH) as an oxidant. The presence of coordinatively unsaturated metal sites in UoB‐5 could be the reason for high performance in this reaction. Furthermore, using the long linker with the free ‐NC group and uncoordinated ‐N atom on the wall of the pores created UoB‐5 an excellent candidate for the catalytic activities without activation of the framework. It was confirmed with the heterogeneous catalytic experiments on the one‐pot tandem synthesis of imines from benzyl alcohols and anilines. Eventually, the new Cu‐MOF (UoB‐5) could be an alternative catalyst as a more economically favorable and environmentally friendly in the catalysis field. Abstract : The synthesis and characterization of novel Cu‐MOF based on a new Schiff‐base as linker. The high performance of the synthesized Cu‐MOF as a heterogeneous catalyst in alcohol oxidation and one‐pot tandem synthesis of imines.